Integrated Sensing and Communication Waveform Design With Sparse Vector Coding: Low Sidelobes and Ultra Reliability - Zhang, Ruoyu; Shim, Byonghyo; Yuan, Weijie; Renzo, Marco Di; Dang, Xiaoyu; Wu, Wen (IEEE transactions on vehicular technology, 2022)
Integrated sensing and communication (ISAC) can provide efficient usage for both spectrum and hardware resources. A critical challenge, however, is to design the dual-functional waveform for simultaneous radar sensing and communication. In this paper, we propose a sparse vector coding-based ISAC (SVC-ISAC) waveform to simultaneously provide low sidelobes for radar sensing and ultra reliability for communication transmission. The key idea of the proposed waveform is to embed the communication information into the support of one sparse vector and transmit a low-dimensional signal via the spreading codebook. We derive a closed-form expression of the ambiguity function for the proposed SVC-ISAC waveform, and prove that it exhibits low sidelobes in the delay and Doppler domains, regardless of the distribution of the transmitted bit stream. In addition, the information decoding at the communication receiver is solved through the support identification and sparse demapping. Simulation results demonstrate that the proposed waveform improves the reliability while consistently suppressing the sidelobe levels.